The Abundance of Genes Encoding ESBL, pAmpC and Non-β-Lactam Resistance in Multidrug-Resistant Enterobacteriaceae Recovered From Wastewater Effluents - Fadare, Folake Temitope; Okoh, Anthony Ifeanyi (Frontiers in Environmental Science, 2021)
The aquatic environments play a critical function in the widespread of antibiotic-resistant bacteria, ultimately impacting human health. We evaluated the abundance of Enterobacteriaceae and the various resistance gene determinants in final effluents of wastewater treatment plants (WWTPs) in the Eastern Cape Province, Republic of South Africa. A total of 44 presumptive Enterobacteriaceae was recovered following standard isolation methods. Upon molecular confirmation through Matrix-Assisted Laser Desorption/Ionization Time of flight (MALDI TOF), a high predominance of Klebsiella pneumoniae (24%) was noted. All the confirmed isolates (n=29) subjected to a panel of eighteen antibiotics categorized into eleven different classes were multidrug-resistant (MDR). They displayed resistance against antibiotics in more than three different classes. Notably, one E. cloacae exhibited resistance against all the antibiotics assayed. The multiple antibiotic resistance indices (MARI) ranged from 0.22 to 1.0, indicating an environment with high pressure of antibiotics. Conventional PCR analysis showed that 72.4% of the isolates harboured at least one β-lactamase genetic determinant. The most predominant extended-spectrum β-lactamases were blaCTX-M-group (21.5%), blaTEM (20%), and blaSHV (16.9%) while the most predominant plasmid-mediated AmpC-type β-lactamases were blaCIT and blaACC (25.9%) and blaEBC (22.2%). A total of 86.2% of the Enterobacteriaceae harboured a minimum of one non-β-lactam resistance gene determinant with predominance observed in catII (25%), sulII (15.8%), and sulI (14.5%). These results demonstrate an abundance of MDR Enterobacteriaceae in WWTPs' effluents. The study confirms the need to optimize current WWTPs' processes to improve the quality of effluents and ultimately reduce the potential risks of using such water when discharged into the environment.